2019
DOI: 10.1111/hepr.13452
|View full text |Cite
|
Sign up to set email alerts
|

Favorable radiological antitumor response at 2 weeks after starting lenvatinib for patients with advanced hepatocellular carcinoma

Abstract: Aim We aimed to investigate the radiological antitumor response at 2 weeks after starting lenvatinib for patients with advanced hepatocellular carcinoma in real‐world practice. Methods This retrospective study enrolled 40 patients who received lenvatinib. Radiological antitumor response was evaluated according to the modified Response Evaluation Criteria in Solid Tumors. Results The objective response rate at 2 weeks and best overall response on confirmation of complete response, partial response (PR), and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…[ 8 10 ] It has also been reported that the relative dose intensity (RDI) plays an important role in the therapeutic effect of LEN. [ 8 , 11 , 12 ] In all of our cases, hepatic reserve function was good and the RDI, up to the first imaging evaluation, was high (Case 1: 75%, Case 2: 100%, Case 3: 100%) (Table 1 ). Although in BCLC stage B, cTACE/TAE is a standard treatment for unresectable HCC, Arizumi et al and Ogasawara et al reported that the switch from cTACE to SOR significantly improved the OS in patients with intermediate-stage HCC who were refractory to cTACE therapy.…”
Section: Discussionmentioning
confidence: 69%
“…[ 8 10 ] It has also been reported that the relative dose intensity (RDI) plays an important role in the therapeutic effect of LEN. [ 8 , 11 , 12 ] In all of our cases, hepatic reserve function was good and the RDI, up to the first imaging evaluation, was high (Case 1: 75%, Case 2: 100%, Case 3: 100%) (Table 1 ). Although in BCLC stage B, cTACE/TAE is a standard treatment for unresectable HCC, Arizumi et al and Ogasawara et al reported that the switch from cTACE to SOR significantly improved the OS in patients with intermediate-stage HCC who were refractory to cTACE therapy.…”
Section: Discussionmentioning
confidence: 69%
“…Many investigators have reported that AFP reduction after systemic therapy, such as sorafenib and lenvatinib, was a useful prognostic marker of good outcomes (8,14). The REACH-2 trial was the first to show efficacy with a biomarker AFP level of ≥400 ng/ml, it documented that AFP level at baseline was a prognostic factor related to OS, but it did not document AFP response (1).…”
Section: Discussionmentioning
confidence: 99%
“…According to the clinical practice guidelines on the management of HCC (3,4), both sorafenib and lenvatinib were recommended as the first-line systemic therapy options for patients with advanced stage HCC. Because the REFLECT trial reported superior antitumor response and progression-free survival (PFS) with lenvatinib over sorafenib (5,6), lenvatinib has been increasingly selected as the first-line therapy in clinical practice (7)(8)(9)(10). However, the outcomes of ramucirumab treatment after lenvatinib failure are unknown, because the REACH-2 trial was conducted on patients with prior sorafenib intake (1).…”
mentioning
confidence: 99%
“…With LEN therapy, however, we have sometimes experienced that tumor growth occurs despite disappearance of arterial tumor enhancement, or that arterial tumor enhancement reappears soon after LEN interruption [28]. Kuzuya et al indicated that a good radiologic antitumor response, based on the mRECIST (i.e., almost complete disappearance of arterial tumor enhancement), might not necessarily imply tumor necrosis, especially soon after LEN initiation [29]. Thus, it is sometimes difficult to clearly distinguish between viable tumor tissue and necrotic tissue during the early phase of treatment.…”
Section: Discussionmentioning
confidence: 99%